Mastery in distance learning, effectiveness and equity. The point of view of teachers in the SIRD survey in Emilia-Romagna - Ciani , Andrea; Ricci , Aurora; Vannini , Ira (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
The article presents a research carried out on 93 university students of a master degree in education on This paper is a focus of the SIRD National Survey on Distance Learning (DL) on the reality of teachers in Emilia-Romagna. A total of 3.423 in-service teachers in the region (or 6% of total teachers in the region) participated in the survey, out of 16.133 teachers participating nationally. Teachers responded to an online questionnaire during the first 2020 lockdown in Italy. This observational research aims to explore teachers' perceived differences in levels of DL’s criticality and resources, and levels of evaluation of effectiveness for learning and inclusion. These insights were conducted by considering different conditions of mastery in DL (lack of training, training, lack of experience, experience, mastery). It went on to explore the models that best predict perceptions of effectiveness for learning and inclusion among the five mastery conditions in DL. Descriptive analyses and multiple stepwise regression analyses were performed. The results show that the teachers' DL mastery condition corresponds, with significant differences from the other conditions, to lower levels of criticality and a more positive perception of potential resources. In addition, it emerges the central role of the perception of adequate assessment to ensure effectiveness for learning and inclusion of all students. It seems useful to imagine future training courses for teachers who know how to combine theoretical preparation with practical experience in supervised DL, possibly linked to moments of assessment for learning or as learning.